Integrative analysis of T cell-associated markers in Ewing sarcoma reveals prognostic signatures and immune dynamics - Saddozai, Umair Ali Khan; Liu, Chenxu; Yan, Fei; Lu, Zhendong; Khawar, Muhammad Babar; Akbar, Muhammad Usman; Khattak, Saadullah; Sun, Haibo; Yang, Ping (Frontiers in Immunology, 2025)
BackgroundEwing sarcoma (ES) is a rare and aggressive pediatric bone malignancy with poor prognosis, driven by therapy-resistant tumor microenvironments (TME). The TME plays a critical role in tumor progression through a complex and dynamic network of reciprocal interactions among immune cells (dysfunctional T cells, immunosuppressive macrophages), stromal components (cancer-associated fibroblasts), and tumor cells. These interactions collectively shape the immune landscape, promote immune evasion, and contribute to therapeutic resistance. Identifying reliable prognostic markers remains a critical challenge.MethodsHere we performed an integrated single-cell RNA sequencing, WGCNA, and bulk RNA-seq analyses to investigate tumor-immune interactions. Differentially expressed genes (DEGs) intersected with T cell markers identified a total of 174 T cell-associated genes. Functional enrichment analysis and molecular subtyping were performed to explore immune-related pathways. A prognostic model based on CLEC11A, BDP1, and ID3 was constructed using Cox regression and validated in external datasets. Immune infiltration was assessed using the CIBERSORT algorithm.ResultsT cell marker analyses revealed key roles in pathways such as PI3K-Akt signaling and immune modulation. Molecular subtyping identified two clusters with distinct immune microenvironments: Cluster C1 (immunosuppressive phenotype and poorer prognosis) and Cluster C2 (functionally active immune profile associated with better prognosis). The prognostic model demonstrated high predictive accuracy for 1-, 3-, and 5-year survival (AUC: 0.85, 0.82, 0.78). Additionally, a higher tumor mutation burden (TMB) with low survival rate has been observed in High-risk group. Immune infiltration analysis showed higher CD8+ T cell and dendritic cell activity and immune checkpoint expression in low-risk groups. Experimental validation demonstrated that ID3 silencing inhibited tumor cell proliferation and induced cell cycle arrest in ES cell lines.ConclusionTogether, our study identified CLEC11A, BDP1, and ID3 as key T cell associated prognostic markers and developed a validated model to predict survival outcomes in ES. Insights into T cell markers and tumor-immune dynamics offer promising advances in prognostic assessment and immunotherapy for ES. Furthermore, the role of ID3 in immune evasion and tumor proliferation underscores its potential as a therapeutic target, providing new avenues for immune checkpoint regulation and personalized treatment strategies.